The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Publisher: Academic Journals KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 10.5897/err2015.2523 10/gjj9dr 2339240:ZXNUGEXT 2405685:SHM89EW9
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Publisher: Academic Journals KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 10.5897/err2015.2523 10/gjj9dr 2339240:ZXNUGEXT 2405685:SHM89EW9
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

Survey of the Use of Assistive Technology in Schools in Nigeria - Ajuwon, Paul M.; Chitiyo, George (Journal of the International Association of Special Education, 2015)
In this study, the researchers explored the state of the use of assistive technology (AT) in Nigeria through a survey of 165 special educators. The underlying structure of the respondents' perceptions, and their challenges and barriers to the use of AT, were examined. Among other findings, the largest proportion of students using AT are those with deafness or hearing impairment (53.3%), followed by those with a learning disability (40%). Training in the use of AT lags behind, with most professionals having received little or no training in the use of AT. The lack of appropriate AT devices and services in classrooms, and irregular electricity to operate available devices, were frequently cited as the biggest challenges regarding AT. Correlations between students' conditions and factors of teachers' perceptions suggested the need to make AT available for students with certain conditions, as well as the need for effective training for teachers.
KerkoCite.ItemAlsoKnownAs: 2339240:2B5LKGDA 2405685:XS664IV7
Keywords: Access to Computers; Assistive Technology; Barriers; Computer Uses in Education; Deafness; Disabilities; Educational Technology; Energy; Faculty Development; Foreign Countries; Hearing Impairments; Learning Disabilities; Likert Scales; Special Education Teachers; Statistical Analysis; Teacher Competencies; Teacher Surveys; Technological Literacy; Training; ⛔ No DOI found

Why people use and don’t use technologies: Introduction to the special issue on assistive technologies for cognition/cognitive support technologies - Scherer, Marcia J.; Federici, Stefano (NeuroRehabilitation, 2015)
This special issue focuses on assistive technologies for cognition/cognitive support technologies as well as the ways in which individuals are assessed and trained in their use. We provide eleven diverse articles that give information on products, why they are used and not used, and best professional practices in service provision. Our goal is to highlight a broad topic that has received limited research investigation and offer an insight into how different countries and programs are promoting access to and use of assistive technologies for cognition/cognitive support technologies
Publisher: IOS Press KerkoCite.ItemAlsoKnownAs: 10.3233/NRE-151264 2339240:RXAAUBQE 2405685:AKMUZPJ4
Keywords: Assistive technology devices; Matching Person and Technology Model; abandonment; assistive technology services; brain injury; cognitive support technologies; nonuse

The effects of a technology-aided learning environment on the improvement of a primary special education school - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people’s expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming ‘learning’ or ‘effective’ schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers’ functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed. Key words: School development, technology, innovation, hearing impaired.
KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 2339240:9SHHNJCH 2405685:WQ7ZLZVW
Keywords: ___working_potential_duplicate

Inclusive education in an international school: A case study from Hong Kong - Chan, T.; Yuen, Mantak (International Journal of Special Education, 2015)
This case study provides an overview of current policy, practices and problems concerning inclusion in one international secondary school in Hong Kong. A total of 13 interviews were conducted with the school management team, teachers, students and parents, supplemented by 12 classroom observations and two ‘student-shadowing’ exercises. Findings suggest that the school has been reasonably successful in raising teachers’ awareness of inclusive education principles, creating a whole-school culture of inclusiveness, and forming a partnership with parents. However, the commitment of individual teachers to implementation of inclusive practices in their own classrooms varies. Some teachers are not adaptive enough in their teaching approach, and have difficulties differentiating instruction and learning activities. Improvements are also needed in the way that teachers work with their education assistants (classroom aides). Implications for improvement are discussed. © 2015, International Journal of Special Education. All rights reserved.
KerkoCite.ItemAlsoKnownAs: 2339240:G6HTWKIA 2405685:5VS97KU6

Special Education and Deaf Children in Pakistan - Akram, Bushra; Bashir, Rukhsana (Journal of Elementary Education, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:9TKMBGYE 2405685:NQQMGAXE
Keywords: ⛔ No DOI found

Towards a Disability Inclusive Education - Sæbønes, Ann-Marit; Bieler, Rosangela Berman; Baboo, Nafisa; Banham, Louise; Singal, Nidhi; Howgego, Catherine; McClain-Nhlapo, Charlotte Vuyiswa; Riis-Hansen, Trine Cecilie; Dansie, Grant Angus (Oslo Summit on Education for Development, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:JPKX5XBG 2339240:SSMZBC9V 2405685:3AIMPPZI 2405685:LDMG6PB8
Keywords: ___working_potential_duplicate

The design and testing of multimedia for teaching arithmetic to deaf learners - Techaraungrong, Piyaporn; Suksakulchai, Surachai; Kaewprapan, Wacheerapan; Murphy, Elizabeth (Education and Information Technologies, 2015)
The purpose of the study reported on in this paper was to design and test multimedia for deaf and hard of hearing (DHH) learners. The study focused on counting, addition and subtraction with grade one (age 7) DHH learners in Thailand. The multimedia created for the study was informed by design considerations for DHH learners of arithmetic and aimed to minimize cognitive load. Testing took place over a period of 16 weeks during which learners alternated between 2 and 3 week sessions of one hour per day with multimedia (numbers 1–10) versus 2–3 week sessions of one hour per day with the teacher (numbers 11–20). Results of the design included features such as non-essential use of text, reliance on non-symbolic objects, user control, and signals to relevant content. Results of testing showed that learning with multimedia resulted in higher scores than learning with the teacher (Z = 4.545, p = 0.000). Post-intervention interviews highlighted the role of motivation, ease of comprehension and independent learner control of the multimedia. The conclusion highlighted the need for multimedia design principles that reflect a more inclusionary focus on children with special needs such as those featured in this study.
8 citations (Crossref) [2024-02-28] KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-015-9441-1 2339240:EEJYTIKF 2405685:DDVUKNXB
Keywords: Arithmetic; Cognitive load; Deaf and hard of hearing; Design; Multimedia; Testing; ⛔ No INSPIRE recid found

Empowering Teachers to Promote Inclusive Education. A case study of approaches to training and support for inclusive teacher practice - Donnelly, Verity (European Agency for Special Needs and Inclusive Education, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:WMMVHIHD 2405685:ERPJWFQ4